Cleanliness assessment of Lake Toba tourist attractions from stakeholders' perspective. Issue 1 (1st October 2022) - Khair, H; Utami, R; Lordye, G; Sari, U; Pasaribu, E
Abstract: Lake Toba area is one of the priorities for developing tourist destinations in Indonesia. As a strategic national tourism area, it is necessary to identify aspects of the tourism area development that are not yet optimal to increase the number of tourist visits to that location. This study aims to assess the cleanliness of tourist sites in Lake Toba based on the assessment of tourism site stakeholders, namely visitors, local businesses, and cleanliness managers. The tourist sites in Lake Toba studied were Pasir Putih and Bukit Holbung. This study found that Pasir Putih and Bukit Holbung were considered dirty, with a cleanliness index of 2.63 and 2.60. The assessment shows that access to the cleaning facilities in the two tourist sites is difficult to reach. However, regarding the completeness of the cleaning facilities, Pasir Putih is considered better with an average index of 2.94 compared to the cleaning facilities in Bukit Holbung, which are considered inadequate with an average index of 2.43. The number of tourists visiting a tourist site is directly proportional to the waste generated, and the habits of tourists who visit also affect the cleanliness of a tourist site.